Pelatihan Dan Pendampingan Manajemen Usaha Wisata Edukasi “Kampung Lele” di Kabupaten Kediri Pada Masa Pandemi Covid-19 - Ahmad Yani; Aprilia Dian Evasari; Nurali Najibul Zamzami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The implementation of community service involves the "Kampung Lele" Educational Tour as a partner located in Tales Village, Ngadiluwih District, Kediri Regency. Partners are Micro, Small and Medium Enterprises (MSMEs) that have businesses in the maintenance, processing and educational tours of catfish. During the Covid-19 pandemic, activities at Kampung Lele continued even though there were fewer visitors. Currently Kampung Lele is also running a food delivery order system made from catfish. The problems that occur are the lack of variants of processed products, unattractive packaging, not having structured financial reports and lack of product marketing. The solutions offered are providing education and training related to the management of processed food production made from catfish, packaging design training, providing assistance and training related to making simple financial reports, HR training and appropriate marketing strategies, especially through social media. The methods used are participatory methods, counseling, training and mentoring. The results obtained from the implementation of this community service are that partners get knowledge transfer on making new products, are able to make attractive product packaging and labeling, are able to make simple financial reports, knowledge in HR job training and do online product marketing through social media.